Pengaruh Bauran Pemasaran Jasa Terhadap Kepuasan Tamu Hotel Grand Orri Berastagi - conie sitepu; Vionika Sari Tarigan (Universitas Quality, 2021)
The purpose of the study was to determine the effect of the service marketing mix (Price,Place,and Process) on guest satisfaction tthe Grand Orri Hotel Berastagi.The type of research used was a quantitative approach. The sample used was 95hotel guests as respondents. The data collection technique used a questionnaire. The data analysis technique used multiple linear regression test, partialtest (test),model test (F test). The results of multiple linear regression analysis Y = 28,863+2,398X1+1,338X2+ 1,382X3+e. The results showed that the price variable, place and process have a significant effect on guest satisfaction. This can be proven from the F test. The results of the F test simultaneously show that price, place, an dprocess have a significant influence on guest satisfaction where Fcount > Ftable(469.488>2.705).Thus price,place and location simultaneously have a significant effect on guest satisfaction at Grand Orri Berastagi Hotel. ses) is able to explain the dependent variable (guest satisfaction) of 93.7% and as much as 6.3% of the guest satisfaction variable isex plained by other variables outside of this study.